Technology of Cognitive Management in the Digital Economy - N. M. Abdikeev (Мир новой экономики)
Technological transformation processes allow you to move to a qualitatively new level of business technology. This suggests that the occurrence of so-called cognitive era. In these circumstances, the development of new management technologies and approaches in management, in particular, the cognitive management. Discusses the application of cognitive technologies business process management in the digital economy.